2015
DOI: 10.1039/c5lc01045d
|View full text |Cite
|
Sign up to set email alerts
|

Single chip SPR and fluorescent ELISA assay of prostate specific antigen

Abstract: A multi-channel system combining fluidics and micropatterned plasmonic materials with wavelength interrogation surface plasmon resonance (SPR) and fluorescence detection was integrated from the combination of a small and motorized fluorescence microscope mounted on a portable 4-channel SPR instrument. The SPR and fluorescent measurements were performed based on the same detection area in a multi-channel fluidic, with a sensing scheme for prostate-specific antigen (PSA) consisting of a sandwich assay with a cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 51 publications
0
47
0
Order By: Relevance
“…While their platform provides an overall detection strategy on bead‐based technology, our device offers a general enrichment method for sample preconcentration. Breault‐Turcot et al, employing a combination of surface plasmon resonance and fluorescence to detect PSA, attained a detection limit of 10 pM (0.3 ng mL −1 ) . Sanghavi et al using nanoslit and nDEP to enrich PSA biomarker demonstrated a sensitivity level of 5 pg mL −1 , while the fabrication of their device involved complex electron beam lithography .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While their platform provides an overall detection strategy on bead‐based technology, our device offers a general enrichment method for sample preconcentration. Breault‐Turcot et al, employing a combination of surface plasmon resonance and fluorescence to detect PSA, attained a detection limit of 10 pM (0.3 ng mL −1 ) . Sanghavi et al using nanoslit and nDEP to enrich PSA biomarker demonstrated a sensitivity level of 5 pg mL −1 , while the fabrication of their device involved complex electron beam lithography .…”
Section: Resultsmentioning
confidence: 99%
“…Breault-Turcot et al, employing a combination of surface plasmon resonance and fluorescence to detect PSA, attained a detection limit of 10 pM (0.3 ng mL −1 ). [38] Sanghavi et al using nanoslit and nDEP to enrich PSA biomarker demonstrated a sensitivity level of 5 pg mL −1 , while the fabrication of their device involved complex electron beam lithography. [22] Therefore, the device reported here exhibits comparable or higher sensitivity in detecting real samples for clinical use.…”
Section: Immunoassaysmentioning
confidence: 99%
“…In previous work, the detection of prostate specific antigen (PSA) was achieved using a multi-channel Lab-on-a-chip (LoC) system which combined micropatterned plasmonic materials with K-SPR, fluorescence detection and microfluidics. The dual SPRfluorescence assay detected PSA at concentrations of 10 pM to 50 nM with an analysis time of 12 min which was relevant for clinical diagnostics (Breault-Turcot et al 2015). Various miniaturized K-SPR biosensors utilizing microfluidics for PoC applications with low detection limits and quick analysis have also been researched previously (Wang & Fan 2016).…”
Section: Introductionmentioning
confidence: 99%
“…14 Various microuidics-based immunoassay methods have been developed to address the limitations of conventional assay platforms. They exploited a variety of different approaches, such as the automated lab-on-a-disc devices, 15,16 integration of an optical system in the microuidic devices, [17][18][19] a quantum dot (QD) "barcoding" system, 20,21 and the three-dimensional microuidic connement. 22,23 Despite considerable efforts in the microuidic immunoassay platforms in the past decades, most researches have focused on automation, [24][25][26] increased surface areas, 27,28 improved reporter probes, 29,30 and distinctive detection principles; 31,32 however, the efficient delivery of antibody reagents to the reaction sites has been rarely explored.…”
Section: Introductionmentioning
confidence: 99%